2019
DOI: 10.1016/j.ejpb.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Tumor recognition of peanut agglutinin-immobilized fluorescent nanospheres in biopsied human tissues

Abstract: We are investigating an imaging agent for early detection of colorectal cancer. The agent, named the nanobeacon, is coumarin 6-encapsulated polystyrene nanospheres whose surfaces are covered with poly(N-vinylacetamide) and peanut agglutinin that reduces non-specific interactions with the normal mucosa and exhibits high affinity for terminal sugars of the Thomsen-Friedenreich antigen, which is expressed cancer-specifically on the mucosa, respectively. We expect that cancer can be diagnosed by detecting illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Peanut agglutinin (PNA) is a homotetrameric plant agglutinin extracted from peanuts that can bind to a variety of disaccharides containing β-D-galactosyl-(1–3)-N-acetyl-D-galactosamine [Gal-β(1–3)GalNAc]. Studies have found that the core component of the TF structure is Gal-β(1–3)GalNAc, which is the core structure of MUC1 ( Beack et al, 2017 ; Kumagai et al, 2019 ). Therefore, PNA-modified liposomes can actively target MUC1-positive colorectal cancers to deliver drugs centrally.…”
Section: Introductionmentioning
confidence: 99%
“…Peanut agglutinin (PNA) is a homotetrameric plant agglutinin extracted from peanuts that can bind to a variety of disaccharides containing β-D-galactosyl-(1–3)-N-acetyl-D-galactosamine [Gal-β(1–3)GalNAc]. Studies have found that the core component of the TF structure is Gal-β(1–3)GalNAc, which is the core structure of MUC1 ( Beack et al, 2017 ; Kumagai et al, 2019 ). Therefore, PNA-modified liposomes can actively target MUC1-positive colorectal cancers to deliver drugs centrally.…”
Section: Introductionmentioning
confidence: 99%